i-Rheo: Measuring the materials' linear viscoelastic properties “in a step”! - Daniel Curtis (Journal of Rheology, 2016)
A new analytical technique for determining a materials' linear viscoelastic properties from a simple step-strain measurement is reported. The technique avoids the need for idealisation of real measurements. The technique involves evaluating the Fourier transforms of raw experimental data describing both the time-dependent stress and strain functions. A comparison with conventional linear oscillatory measurements for a diverse range of complex materials is made and the technique is shown to be superior to existing linear oscillatory measurements in all cases.